Investment Decision: The Role of Financial Literacy and Financial Technology (Fintech) - Zakiatul Hidayah, Zulfa; Latif, Abdul; Meirani, Nadia (Economic Education Analysis Journal, 2024)
The purpose of investing is to make a profit. The millennial generation is a generation that knows a lot about finance and tends to be good at managing their money and can anticipate financial problems in the future. This study aims to see how financial literacy and financial technology affect a person's investment decisions, especially an employee in determining the form of investment. The population used is all employees in the Bekasi area. The data source for this study uses primary data obtained from the results of distributing questionnaires using Google Form. The sampling technique using the Lemeshow formula on the millennial generation in the Bekasi area received 192 questionnaires with Linkert scale measurements. The research conducted by the researcher is to measure the positive influence of several indicators on each variable in it using a statistical test tool with Partial Least Square (PLS) using SmartPLS software. The results of the research conducted show that the financial literacy variable is a factor that significantly influences individual investment decisions, in addition, the financial technology variable also influences individual decisions to invest.